MIPO vs. nail for extra-articular distal tibia fractures and the effect of intra-operative alignment control. (28th May 2021) - Bleeker, N J; van Veelen, N; van de Wall, B; Link, B -C; Babst, R; Knobe, M; Beeres, F
Abstract: Objective: Definitive treatment of distal extra-articular fractures of the tibia is challenging and both minimal invasive plate osteosynthesis (MIPO) and intramedullary nailing (IMN) are considered feasible surgical modalities with their own implant-specific merits and demerits. This retrospective study was designed to compare MIPO versus IMN in terms of fracture healing, complications, functional and radiological outcomes and to assess the efficacy of intra-operative alignment control in order to reduce the rate of malalignment after definitive fixation of distal extra-articular fractures of the tibia. Methods: All consecutive adult patients with extra-articular distal meta- or diaphyseal tibia fractures that were treated in a level 1 trauma center in Switzerland between January 2012 and September 2019 either with plating or IMN were included. Outcome measures included fracture healing, complications (infection, malalignment, subsequent sur-geries), functional and radiological outcomes. Intra-operative alignment control encompassed bilateral draping of the lower extremities. Results: A total of 135 patients were included out of which seventy-two patients (53%) were treated with MIPO and 63 patients (47%) underwent IMN. There was a significantly higher incidence of non-union for fractures treated with an IMN (13 (22%) vs. 4 (6%), p = 0.037). There was no significant difference between both groups in terms of rotational malalignment (4% vs. 9%) and angular malalignment (4% vs. 5%). The incidence of malalignment in both groups was lower than reported in literature. A significantly higher rate of infection was found after MIPO (13% vs. 6%, p = 0.028). No differences were found in subsequent surgeries or functional outcomes. Conclusion: Both MIPO and IMN are reliable surgical techniques. IMN is associated with higher rates of non-union whereas MIPO results in a higher risk for infection. The incidence of malalignment was surprisingly low endorsing the utility of the intra-operative alignment control.